Lotus root fiber scaffold as well as preparation method and application thereof
By using 3D printing technology of lotus root fiber as the base material to prepare lotus root fiber scaffolds, the problems of insufficient biocompatibility, degradability and mechanical properties of existing bone repair scaffold materials are solved, and the bone defect healing efficiency is improved.
Patent Information
- Application Number
- CN202510478591.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2025-07-29
AI Technical Summary
The existing bone repair stent materials have problems such as insufficient donor source, immune rejection, high cost, poor biocompatibility, mismatch of degradation rate and bone tissue regeneration rate, and insufficient mechanical properties, resulting in poor bone defect repair effect.
Lotus root fibers are used as the base material to prepare lotus root fiber scaffolds through 3D printing technology. The biocompatibility and degradability of lotus root cellulose are used to dissolve at low temperatures and a personalized porous scaffold is printed to adapt to the shape and mechanical properties of bone defects.
It has achieved bone repair scaffolds with good biocompatibility and appropriate degradation rate, promoted cell growth and angiogenesis, improved bone defect healing efficiency, and solved the problem that traditional scaffold materials cannot take into account both the mechanical strength and biodegradability.
Smart Images

Figure CN120381556A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of bone repair scaffolds, and more specifically, relates to a lotus root fiber scaffold, a preparation method thereof, and an application thereof. Background Art
[0002] The bone healing process is divided into four consecutive but partially overlapping stages, including hematoma inflammation, soft callus formation, hard callus formation, and bone remodeling. Therefore, the difficulties in bone defect treatment are mainly reflected in three aspects: First, the self-healing ability of bone tissue is limited, and critical-sized defects cannot be repaired by themselves; Second, the existing scaffold materials for bone defect repair are mostly allogeneic bone, xenogeneic allogeneic bone, metal scaffolds, bioglass, high-strength hydrogels, etc., and most of them are prefabricated. Autologous and allogeneic bone are currently the gold standard for treating bone defects, but there are significant limitations - autologous bone transplantation faces insufficient donor sources (satisfaction rate < 30%), allogeneic bone transplantation has immune rejection reactions (incidence rate > 15%) and the risk of disease transmission, and is costly, with poor adhesion; Third, the morphological adaptability problem of irregular bone defects leads to a low matching success rate of traditional restorations. Thus, most traditional scaffolds have poor immunogenicity, high costs, complex preparation processes, troublesome operations, and insufficient biocompatibility, which affect the repair efficiency of bone defects; The degradation rate does not match the bone tissue regeneration rate, hindering the growth rate and space of new tissues during bone repair, resulting in poor bone repair effects, and requiring secondary surgery for removal, increasing pain and economic burden; In addition, the performance of the scaffold materials prepared by the existing technology in clinical applications is still not satisfactory, especially in the repair of complex irregular bone defects, there are problems of poor interface matching between the scaffold and the host bone. Injectable materials such as bone cement and hydrogels can achieve morphological adaptation to the defect site through minimally invasive methods, but their inherent mechanical property defects and low porosity characteristics are not conducive to cell growth and angiogenesis. Most natural polymer scaffold materials face problems such as incompatibility between mechanical strength and degradation performance, severely restricting their application scope in clinical practice.
[0003] In recent years, cell therapy based on human mesenchymal stem cells (hMSCs) has shown good tissue repair potential. However, directly injecting hMSCs into damaged tissues will result in low cell survival rate, implantation rate, and insufficient directional differentiation ability, thus limiting its therapeutic effect in clinical practice. Therefore, developing new stem cell scaffold materials with high bone induction activity will become a breakthrough point for solving the key problems in bone regenerative medicine in the future industry.
[0004] 3D printing technology exhibits unique advantages in the field of bone tissue engineering. Its core lies in the ability to fabricate personalized scaffolds that highly match the morphology of the patient's bone defect. By precisely controlling the macroscopic geometric shape and microscopic structural features of the scaffolds, this technology can not only perfectly adapt to the anatomical morphology of complex and irregular bone defects but also construct a three-dimensional microenvironment conducive to cell migration, blood vessel growth, and tissue regeneration. In recent years, researchers have developed various 3D printing scaffold systems, including natural polymers (such as chitosan, chitin, sodium alginate, etc.), synthetic polymers (such as polycaprolactone, polylactic acid, polyamide, photosensitive resin, etc.), and inorganic materials (such as bioceramics, hydroxyapatite, bioactive glass, metallic materials, etc.). However, the existing material systems still have significant limitations. Among them, natural polymer materials such as collagen have the risk of antigenicity, and their degradation behavior is difficult to precisely regulate; while synthetic polymers such as polylactic acid produce acidic products during the degradation process, leading to local inflammatory reactions. Therefore, the development of new 3D printing scaffold materials with good biocompatibility, controllable degradability, and suitable mechanical properties remains the key research direction at present.
[0005] In summary, aiming at the problems that the current allogeneic bone, xenogeneic bone have limited sources, high costs, poor adhesion, scarce donors, and poor immunogenicity, the prefabricated scaffold materials have high strength but poor adaptability, insufficient biocompatibility, large surgical exposure area, the degradation rate of the scaffold material does not match the growth rate of the newly formed bone tissue, increasing bone loss, and secondary surgery, etc., which increase the patient's recovery time and pain, restricting their practical applications. At present, it is urgent to propose a lotus root fiber scaffold, its preparation method, and its application as a scaffold for the preparation of bone repair. Summary of the Invention
[0006] The object of the present invention is to propose a lotus root fiber scaffold, its preparation method, and its application in view of the deficiencies of the prior art. The scaffold obtained by the present invention has an appropriate degradation rate and biocompatibility, does not cause problems such as inflammation, and has a suitable mechanical strength, which can greatly improve the bone defect healing efficiency.
[0007] To achieve the above object, in the first aspect of the present invention, a preparation method of a lotus root fiber scaffold is provided. The preparation method includes the following steps:
[0008] S1: Peel and remove the joints of fresh lotus roots that have been washed, obtain the edible part and cut it into thin slices; sequentially perform drying, pulverization, and sieving on the thin slices to obtain lotus root whole powder;
[0009] S2: Dry and pulverize the lotus root skin and joints obtained in step S1 to obtain lotus root residue powder; mix the lotus root residue powder, water, and amylase, and perform starch removal treatment to obtain pretreated lotus root residue; sequentially perform alkali treatment, bleaching treatment, and drying treatment on the pretreated lotus root residue to obtain lotus root residue cellulose powder;
[0010] S3: Mix lotus root whole powder, lotus root residue cellulose powder, alkali, urea and water at low temperature and stir them. Repeat the freezing and thawing process multiple times, and then centrifuge to obtain a transparent solution (i.e., lotus root cellulose-lotus root whole powder-based printing ink).
[0011] S4: Use the transparent solution to print a lotus root-based scaffold through three-dimensional inkjet printing technology, obtain a printed scaffold structure, and soak it in an ethanol aqueous solution for curing and regeneration to obtain a lotus root fiber scaffold.
[0012] According to the present invention, preferably, in step S1:
[0013] The thickness of the thin slice is 2-3 mm;
[0014] The drying treatment is to lay the thin slice flat in a hot air drying oven at 40-100 °C and dry it for 6-10 h;
[0015] The sieving treatment is to sieve the pulverized lotus root powder through a 110-130 mesh sieve to obtain lotus root whole powder.
[0016] According to the present invention, preferably, in step S2:
[0017] The drying temperature is 60-70 °C;
[0018] The material-liquid ratio of the lotus root residue powder to water is 1:(8-12) g / mL; the mass concentration of the amylase in the mixed system composed of the lotus root residue powder, water and amylase is 0.15%-0.25%;
[0019] The starch removal treatment includes: subjecting the mixed system composed of the lotus root residue powder, water and amylase to a water bath at 50-60 °C for 3-5 h to obtain a starch-removed lotus root residue system; subjecting the starch-removed lotus root residue system to a water bath at 85-95 °C for 1.5-2.5 h, then centrifuging at 4000-5000 rpm and retaining the precipitate, and drying at 45-55 °C to obtain pretreated lotus root residue;
[0020] The alkali treatment includes: mixing and stirring the pretreated lotus root residue with an aqueous sodium hydroxide solution and sodium sulfite powder, filtering and washing (washing until neutral, 3 times) to obtain alkali-treated lotus root residue;
[0021] The bleaching treatment includes: mixing the alkali-treated lotus root residue with an aqueous hydrogen peroxide solution, filtering and washing (washing until neutral) to obtain bleached lotus root residue;
[0022] The drying treatment includes: freeze-drying the bleached lotus root residue in a vacuum to obtain the lotus root residue cellulose powder.
[0023] According to the present invention, preferably, the starch removal treatment further includes performing an iodine solution test on the starch-removed lotus root residue system. After the test system does not turn blue, the starch-removed lotus root residue system is then water-bathed at 85 - 95 °C for 1.5 - 2.5 h.
[0024] According to the present invention, preferably, in the alkali treatment:
[0025] The dosage ratio of the pretreated lotus root residue, sodium hydroxide aqueous solution, and sodium sulfite powder is (8 - 12):(250 - 350):(35 - 40) g / mL / g, and the mass concentration of the sodium hydroxide aqueous solution is 4.5% - 5.5%;
[0026] The temperature of the mixing and stirring is 75 - 85 °C, and the time is 110 - 130 min.
[0027] According to the present invention, preferably, in the bleaching treatment: the mass concentration of the hydrogen peroxide aqueous solution is 3.5% - 4.5%.
[0028] According to the present invention, preferably, in step S3:
[0029] Based on the total weight of the mixed system composed of the lotus root whole powder, lotus root residue cellulose powder, alkali, urea, and water, the content of the lotus root whole powder is 2 - 6 wt%, the content of the lotus root residue cellulose powder is 2 - 6 wt%, the content of the alkali is 7.5 - 8.5 wt%, and the content of the urea is 6.5 - 7.5 wt%;
[0030] The alkali is at least one of lithium hydroxide, sodium hydroxide, and potassium hydroxide;
[0031] The temperature of the low-temperature mixing and stirring is -14 °C to -10 °C;
[0032] The freeze-thaw cycle is performed 1 - 3 times;
[0033] The centrifugation rate is 6500 - 7500 rpm.
[0034] According to the present invention, preferably, in step S4:
[0035] The equipment used for printing is a 3D-bioplotter, the printing speed is 10 - 30 mm / s, the printing pressure is 1 - 3 bar, the printing cartridge temperature is -4 to 40 °C, the inner diameter of the used needle is 0.2 - 1.2 mm, and the printing platform temperature is set to 0 - 40 °C;
[0036] The mass concentration of the ethanol aqueous solution is 25 - 95%.
[0037] The second aspect of the present invention provides the lotus root fiber scaffold prepared by the preparation method of the lotus root fiber scaffold described above.
[0038] The third aspect of the present invention provides the use of the lotus root fiber scaffold as a scaffold for preparing a scaffold for treating bone repair.
[0039] The beneficial effects of the technical solution of the present invention are as follows:
[0040] This invention processes biocompatible, low-cost, and biodegradable lotus root into whole powder. The cellulose is extracted from byproducts such as lotus root skin and nodes during processing, fully utilizing the remaining components. The cellulose is dissolved in a low-temperature, alkaline, and urea solution. Combined with 3D printing technology, this method creates a customized bone repair scaffold with adjustable mechanical properties and biodegradability, resolving the conflicting demands of traditional scaffolds for both mechanical strength and biodegradability. The shear extrusion effect of the printing process reshapes the scaffold structure, imparting it with optimal mechanical strength. The porous structure provides space for cell attachment and proliferation, promoting cell growth, angiogenesis, and bone matrix deposition, thereby accelerating bone tissue reconstruction.
[0041] This invention utilizes lotus root, an important component of Hubei Province's top ten agricultural product industry chains (vegetable chain), as the base material, combined with 3D printing technology, to customize high-strength, degradable bone tissue repair materials according to the patient's bone defect conditions, achieving dynamic matching between the material degradation rate and the new bone regeneration rate, thereby improving bone repair efficiency.
[0042] The present invention can utilize the natural fiber of lotus root to solve the problems of poor adhesion and insufficient degradability of current commercial bone repair scaffolds, and produce a bone repair scaffold that takes into account biocompatibility, mechanical adaptability, and degradability. The shape can be customized according to the bone defect, providing attachment and growth space for bone marrow stem cells, reshaping the "bone-flesh connection" microenvironment, and promoting bone defect repair.
[0043] The technology of the present invention can solve the problem of mismatch between the degradability of existing scaffolds and the growth rate of new tissues. The obtained scaffold has a suitable degradation rate and biocompatibility, does not cause inflammation and other problems, has adaptive mechanical strength, and greatly improves the efficiency of bone defect healing.
[0044] Lotus root is rich in natural polysaccharides such as cellulose and starch, and possesses excellent biodegradability. Therefore, the lotus root fiber-based bone repair scaffold of the present invention, due to its inherent biocompatibility and bioactivity, is an ideal biomedical scaffold. In an in vivo mouse skull defect model, it demonstrated excellent potential as a bone repair material, resolving the challenges currently faced by bone repair products on the market, such as the incompatibility between strength and adaptability, as well as the mismatch between degradation rate and bone tissue growth rate. This product has broad application prospects and market value.
[0045] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] The above and other objects, features, and advantages of the present invention will become more apparent by describing the exemplary embodiments of the present invention in more detail with reference to the accompanying drawings, in which, in the exemplary embodiments of the present invention, the same reference numerals generally represent the same components.
[0047] Figure 1 The curve showing the change of the modulus of the lotus root cellulose - lotus root whole powder - based printing ink obtained by the preparation method of a lotus root fiber scaffold provided in Example 1 of the present invention with strain is shown.
[0048] Figure 2 The curve graph showing the change of the viscosity of the lotus root cellulose - lotus root whole powder - based printing ink obtained by the preparation method of a lotus root fiber scaffold provided in Example 1 of the present invention with the shear rate is shown.
[0049] Figure 3 The hybrid lotus root fiber - lotus root whole powder scaffold obtained by the preparation method of a lotus root fiber scaffold provided in Example 1 of the present invention is shown.
[0050] Figure 4 The curve graph showing the swelling behavior of different scaffolds of Example 1 and Comparative Examples 1 - 2 of the present invention is shown.
[0051] Figure 5 The degradation curve graph of different scaffolds of Example 1 and Comparative Examples 1 - 2 of the present invention is shown.
[0052] Figure 6 The compressive strength of different scaffolds of Example 1 and Comparative Examples 1 - 2 of the present invention is shown.
[0053] Figure 7 The process diagram showing the promotion of skull repair by the lotus root cellulose - lotus root whole powder scaffold obtained in Example 1 of the present invention is shown. Detailed Embodiments
[0054] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.
[0055] Example 1
[0056] This example provides a preparation method of a lotus root fiber scaffold, and the preparation method includes the following steps:
[0057] S1: Peel and remove the joints of the washed fresh lotus roots to obtain the edible parts, and cut them into thin slices with a thickness of 2-3 mm. Spread the thin slices in a hot air drying oven at 80 °C and dry for 8 h to obtain dried thin slices, which are then crushed using a crusher, passed through a 120-mesh sample sieve to obtain lotus root whole powder.
[0058] S2: Dry the lotus root peels and joints obtained in step S1 at 65 °C, and then crush them using a pulverizer to obtain lotus root residue powder. Mix the lotus root residue powder, pure water, and amylase, and then perform a water bath at 55 °C for 4 h to remove the raw starch, obtaining a starch-free lotus root residue system (the material-liquid ratio of the lotus root residue powder to water is 1:10 g / mL; the mass concentration of the amylase in the mixed system composed of the lotus root residue powder, water, and amylase is 0.2%). Conduct an iodine solution test on the starch-free lotus root residue system, and the test system does not turn blue. Then, perform a water bath on the starch-free lotus root residue system at 90 °C for 2 h, then centrifuge at 4500 rpm and retain the precipitate, dry it at 50 °C to obtain pretreated lotus root residue. Put 10 g of the pretreated lotus root residue into a dry beaker, add 300 mL of 5% sodium hydroxide aqueous solution and 37.8 g of sodium sulfite powder to the dry beaker, stir at 80 °C for 120 min, filter, wash until neutral, and repeat the treatment 3 times to obtain alkali-treated lotus root residue. Mix the alkali-treated lotus root residue with a 4% hydrogen peroxide aqueous solution, filter and wash until neutral, obtain bleached lotus root residue, and perform freeze-drying in a vacuum to obtain lotus root residue cellulose powder, which is stored in a sealed bag for standby.
[0059] S3: Rapidly mix and stir to dissolve the lotus root whole powder, lotus root residue cellulose powder, lithium hydroxide, urea, and water at a low temperature of -12 °C, perform freeze-thaw cycling twice, and centrifuge at 7000 rpm to obtain a transparent solution (i.e., lotus cellulose-lotus root whole powder-based printing ink).
[0060] Based on the total weight of the mixed system composed of the lotus root whole powder, lotus root residue cellulose powder, lithium hydroxide, urea, and water, the content of the lotus root whole powder is 2 wt%, the content of the lotus root residue cellulose powder is 6 wt%, the content of lithium hydroxide is 8 wt%, and the content of urea is 7 wt%.
[0061] S4: Use the transparent solution to print a lotus root-based scaffold through three-dimensional inkjet printing technology (the printing equipment used is a 3D-bioplotter), obtain a printed scaffold structure, and soak it in a 75% ethanol aqueous solution for curing and regeneration to obtain a high-fidelity lotus root fiber scaffold (i.e., a hybrid lotus fiber-lotus root whole powder scaffold).
[0062] Among them, the printing speed is 15 mm / s, the printing pressure is 2 bar, the printing cartridge temperature is 0 °C, the inner diameter of the used needle is 0.65 mm, and to maintain the stability of the printed structure, the printing platform temperature is set at 30 °C.
[0063] Comparative Example 1
[0064] The difference between this comparative example and Example 1 is only that:
[0065] The lotus root residue cellulose powder, lithium hydroxide, urea and water were rapidly mixed and stirred for dissolution at a low temperature of -12°C, and the freezing and thawing were cycled twice, and then centrifuged at 7000 rpm to obtain a transparent solution (i.e., lotus root cellulose-based printing ink); based on the total weight of the mixed system composed of the lotus root residue cellulose powder, lithium hydroxide, urea and water, the content of the lotus root residue cellulose powder was 8 wt%, the content of lithium hydroxide was 8 wt%, and the content of urea was 7 wt%;
[0066] Using the lotus root cellulose-based printing ink of this comparative example for the printing in step S4, and adopting the same printing conditions as in Example 1, a lotus root cellulose scaffold was obtained.
[0067] Comparative Example 2
[0068] The difference between this comparative example and Example 1 is only that:
[0069] The whole lotus root powder, lithium hydroxide, urea and water were rapidly mixed and stirred for dissolution at a low temperature of -12°C, and the freezing and thawing were cycled twice, and then centrifuged at 7000 rpm to obtain a transparent solution (i.e., whole lotus root powder-based printing ink); based on the total weight of the mixed system composed of the whole lotus root powder, lithium hydroxide, urea and water, the content of the whole lotus root powder was 8 wt%, the content of lithium hydroxide was 8 wt%, and the content of urea was 7 wt%;
[0070] Using the whole lotus root powder-based printing ink of this comparative example for the printing in step S4, and adopting the same printing conditions as in Example 1, a whole lotus root powder-based scaffold was obtained.
[0071] Test Example
[0072] 1. Rheological analysis
[0073] The rheological properties of the lotus root cellulose-whole lotus root powder-based printing ink obtained in Example 1 were measured using a Discovery HR-2 rheometer (TA Instruments, USA). The upper fixture used was a 40 mm diameter flat plate, and the plate spacing was set to 0.5 mm. Before the frequency scan, a strain amplitude scan was first performed to determine the linear viscoelastic region of the lotus root cellulose-whole lotus root powder-based printing ink obtained in Example 1. The steady-state mode was used to measure the apparent viscosity of the ink, and the shear rate ranged from 0.1 - 100 s -1 . During the test, silicone oil was coated on the edge of the lotus root cellulose-whole lotus root powder-based printing ink obtained in Example 1 to prevent water evaporation.
[0074] Results:
[0075] As Figure 1-2As shown, at room temperature, in the low strain range, the storage modulus of the ink is significantly higher than the loss modulus, and the ink exhibits a solid-like state. As the strain increases, the storage modulus drops sharply, and the loss modulus dominates, and the ink exhibits a solution state. A higher storage modulus is beneficial to ensuring the continuous foundation of the ink. With the increase in the shear rate brought about by the printing process, the viscosity of the hybrid lotus fiber-lotus whole powder scaffold drops rapidly, showing obvious shear thinning properties, which facilitates the extrusion of the ink from the needle used and is conducive to the subsequent 3D printing of the formed scaffold.
[0076] As Figure 3 shown, it is the hybrid lotus fiber-lotus whole powder scaffold formed by 3D printing in Example 1. Direct extrusion 3D printing can construct multi-scale structures from the micron scale to the millimeter scale. Taking the lotus cellulose-lotus whole powder-based printing ink of 6wt% lotus residue cellulose powder / 2wt% lotus root whole powder and the needle nozzle with an inner diameter of 0.65mm used in Example 1 as an example, the ink is extruded through the needle used, returns to a solid-like state after the shear is stopped, and then is soaked in 75% ethanol aqueous solution for regeneration to solidify the printed structure, obtaining the hybrid lotus fiber-lotus whole powder scaffold.
[0077] 2. In vitro swelling and degradation performance test
[0078] The swelling ratio and degradation rate of the hybrid lotus fiber-lotus whole powder scaffold obtained in Example 1 were measured by the gravimetric method. In the swelling experiment, the scaffold was soaked in phosphate buffer solution (PBS, pH = 7.4) at 37°C, and the weight of the scaffold was recorded regularly until it no longer changed. In the degradation experiment, the scaffold was soaked in PBS (pH = 7.4) containing lysozyme at 37°C, and shaken at 150 rpm in a 37°C water bath to simulate the movement environment. The scaffold was taken out regularly, dried, and the weight of the scaffold was recorded.
[0079] Results:
[0080] As Figure 4 shown, it is the swelling behavior curve graph of different scaffolds in Example 1 and Comparative Examples 1-2. When the scaffold material is applied in the biomedical field, appropriate swelling behavior is crucial. The scaffold was soaked in phosphate buffer solution until swelling equilibrium was reached. The swelling ratio of the lotus cellulose scaffold in Comparative Example 1 was the lowest, and the swelling ratio of the lotus whole powder scaffold in Comparative Example 2 was the highest. It can be seen that the swelling ratio increases with the increase in the content of lotus whole powder, mainly due to the increase in the concentration of starch in the lotus whole powder. Therefore, the lotus fiber-lotus whole powder scaffold with a certain proportion of cellulose content can firmly resist its swelling behavior.
[0081] As Figure 5As shown, the degradation curves of different scaffolds in Example 1 and Comparative Examples 1-2 are presented. The rapid degradation of the scaffold can cause cells to spread and escape from the targeted site, while an overly slow degradation kinetics will hinder the formation of new bone. The fracture healing time is usually 8 weeks, and a consistent rate of material degradation and new bone formation is the best scenario for bone tissue regeneration applications. It is worth noting that the degradation of the lotus root cellulose scaffold in Comparative Example 1 is slow, approaching 70 days, which may hinder bone tissue regeneration. The degradation cycle of the lotus root whole powder scaffold in Comparative Example 2 is around 20 days, which may result in insufficient tissue support at the bone defect site and cause secondary injury. The degradation cycle of the lotus root cellulose-lotus root whole powder scaffold in Example 1 is around 8 weeks, which is relatively matched with the growth cycle of new bone tissue and is conducive to bone tissue reconstruction.
[0082] 3. Skull Defect Repair Experiment
[0083] After anesthetizing male SD rats (8 weeks old), the skull was exposed through a midline incision along the skin and periosteum of the rats. Two round holes (diameter: 5 mm) were symmetrically drilled on both sides of the midline of the skull. The bone repair material was filled into the round holes of the skull, and then the periosteum and skin were sutured. After the operation, the rats were given analgesic treatment and sacrificed at 4 and 8 weeks respectively. Bruker Micro-CT (skyscan 1276) was used to scan the rat skulls to evaluate the bone defect repair ability. The same scanner parameters (voltage 52 kVp, current 200 μA, scan time 620 ms, resolution 6 μm) were used for all the rat skulls in the experiment. NRecon (Version1.7.4.2, Bruker) software was used to reconstruct the scanned images, and CTvox software (Version3.3.0, Bruker) was used to reconstruct the three-dimensional structure of the bone regeneration area.
[0084] Results:
[0085] As Figure 7 shown, the bone regeneration ability of the lotus root cellulose-lotus root whole powder scaffold in Example 1 was evaluated using a rat skull defect model (d: 5 mm, which cannot heal without intervention). It can be seen that after the treatment process, the scaffold showed good bone tissue regeneration ability, and a large amount of new bone could be observed in the bone defect area. In the late stage of treatment, obvious new bone was visible, and the defect area was completely covered by new bone, indicating that the lotus root cellulose-lotus root whole powder scaffold in Example 1 has excellent bone regeneration ability.
[0086] 4. Compression Test
[0087] As Figure 6As shown, it is the strain intensity diagram of different scaffolds in Example 1 and Comparative Examples 1-2. Mechanical properties are important indicators for evaluating bone repair materials. Compression tests were carried out on the printed porous scaffold materials. Among them, the compression strength of the lotus fiber-lotus whole powder scaffold in Example 1 was 0.85 Mpa, which was higher than that of the lotus whole powder scaffold group in Comparative Example 2. As the content of lotus whole powder increased, the scaffold strength decreased. Therefore, adjustable mechanical strength can be customized according to the bone defect situation.
[0088] The embodiments of the present invention have been described above. The above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations are obvious to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A preparation method of a lotus root fiber scaffold, characterized in that, The preparation method includes the following steps: S1: Peel and remove the joints of fresh lotus roots that have been washed, obtain the edible part and cut it into thin slices; sequentially perform drying, pulverization, and sieving on the thin slices to obtain lotus root whole powder; S2: Dry and pulverize the lotus root peels and joints obtained in step S1 to obtain lotus residue powder; mix the lotus residue powder, water, and amylase, perform starch removal treatment to obtain pretreated lotus residue; sequentially perform alkali treatment, bleaching treatment, and drying treatment on the pretreated lotus residue to obtain lotus residue cellulose powder; S3: Mix and stir lotus root whole powder, lotus residue cellulose powder, alkali, urea, and water at low temperature, cycle through freezing and thawing multiple times, and centrifuge to obtain a transparent solution; S4: Use the transparent solution to print a lotus root-based scaffold through three-dimensional inkjet printing technology, obtain a printed scaffold structure, and soak it in an ethanol aqueous solution for curing and regeneration to obtain a lotus root fiber scaffold.
2. The preparation method of the lotus root fiber scaffold according to claim 1, wherein, In step S1: The thickness of the thin slices is 2 - 3 mm; The drying treatment is to lay the thin slices flat in a hot air drying oven at 40 - 100 °C and dry for 6 - 10 h; The sieving treatment is to pass the pulverized lotus root powder through a 110 - 130 mesh sieve to obtain lotus root whole powder.
3. The preparation method of the lotus root fiber scaffold according to claim 1, wherein, In step S2: The drying temperature is 60 - 70 °C; The material-liquid ratio of the lotus residue powder to water is 1:(8 - 12) g / mL; the mass concentration of the amylase in the mixed system composed of lotus residue powder, water, and amylase is 0.15% - 0.25%; The starch removal treatment includes: placing the mixed system composed of lotus residue powder, water, and amylase in a water bath at 50 - 60 °C for 3 - 5 h to obtain a de-starch lotus residue system; placing the de-starch lotus residue system in a water bath at 85 - 95 °C for 1.5 - 2.5 h, then centrifuging at 4000 - 5000 rpm and retaining the precipitate, and drying at 45 - 55 °C to obtain pretreated lotus residue; The alkali treatment includes: mixing and stirring the pretreated lotus residue with sodium hydroxide aqueous solution and sodium sulfite powder, filtering and washing to obtain alkali-treated lotus residue; The bleaching treatment includes: mixing the alkali-treated lotus residue with hydrogen peroxide aqueous solution, filtering and washing to obtain bleached lotus residue; The drying treatment includes: freeze-drying the bleached lotus residue in a vacuum to obtain the lotus residue cellulose powder.
4. The preparation method of the lotus root fiber scaffold according to claim 3, wherein, The starch removal treatment also includes performing an iodine solution test on the de-starch lotus residue system, and after the test system does not turn blue, then placing the de-starch lotus residue system in a water bath at 85 - 95 °C for 1.5 - 2.5 h.
5. The preparation method of the lotus root fiber scaffold according to claim 3, wherein, In the alkali treatment: The dosage ratio of the pretreated lotus residue, sodium hydroxide aqueous solution, and sodium sulfite powder is (8 - 12):(250 - 350):(35 - 40) g / mL / g, and the mass concentration of the sodium hydroxide aqueous solution is 4.5% - 5.5%; The temperature of the mixing and stirring is 75 - 85 °C, and the time is 110 - 130 min.
6. The preparation method of the lotus root fiber scaffold according to claim 3, wherein, In the bleaching treatment: the mass concentration of the hydrogen peroxide aqueous solution is 3.5% - 4.5%.
7. The preparation method of the lotus root fiber scaffold according to claim 1, wherein, In step S3: Based on the total weight of the mixed system composed of the lotus root whole powder, lotus root residue cellulose powder, alkali, urea and water, the content of the lotus root whole powder is 2-6 wt%, the content of the lotus root residue cellulose powder is 2-6 wt%, the content of the alkali is 7.5-8.5 wt%, and the content of the urea is 6.5-7.5 wt%. The alkali is at least one of lithium hydroxide, sodium hydroxide and potassium hydroxide; The temperature of low-temperature mixing and stirring is -14°C to -10°C; The freeze-thaw cycle is carried out 1-3 times; The centrifugation rate is 6500-7500 rpm.
8. The preparation method of the lotus root fiber scaffold according to claim 1, wherein, In step S4: The equipment used for printing is a 3D-bioplotter, the printing speed is 10-30 mm / s, the printing pressure is 1-3 bar, the printing cartridge temperature is -4 to 40°C, the inner diameter of the needle used is 0.2-1.2 mm, and the printing platform temperature is set at 0-40°C; The mass concentration of the ethanol aqueous solution is 25-95%; 9. A lotus root fiber scaffold prepared by the method for preparing a lotus root fiber scaffold according to any one of claims 1-8.
10. Use of the lotus root fiber scaffold according to claim 9 as a scaffold for preparing a treatment for bone repair.